FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN SUSTAINABILITY REPORT - aurelia clara; susanto salim (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The purpose of this empirical research is to examine the influence of financial performance, leverage, firm size, and the composition of the independent board of commissioners toward sustainability report disclosure. This research uses 81 sample company listed on the Indonesia Stock Exchange in the year of 2017-2019. Sample was selected by using purposive sampling method. Data processing techniques in this research using program Eviews version 11.0. The results of this research indicate that all independent variables simultaneously have a significant effect on stock price volatility. The partial testing shows that financial performance, leverage, and the composition of the independent board of commissioners have an insignificant effect, while firm size has a positive significant effect on sustainability report disclosure. The implication in this research is to increase company awareness to publish a sustainability report.